Meningkatkan Mutu Nilai Kemanusiaan Dan Aktualisasi Sad Kertih Pada Drama Gong Cupak Dadi Ratu - Ni Made Yulianti (Dharma Sastra: Jurnal Penelitian Bahasa dan Sastra Daerah, 2022)
This research examines the drama gong Cupak dadi Ratu Karya Dr. Drs. I Wayan Sugita, M.Si from Drama Gong; in terms of educational aspects, sad kerthi, the success of development in Bali. The topic was chosen with the aim of being able to understand the Text; and explore the contents of the cupak dadi Ratu gong drama which is full of love and social aspects. The problem of this research is that it concerns the social aspects contained in the drama gong Cupak dadi Ratu. The theoretical basis used to solve this problem is the sociology of literature. This research is then divided into three stages, namely: the stage of data collection using observation and interview methods as well as recording and observation techniques virtually, (2) the data processing stage by translating and analyzing, and (3) the stage of presenting the results of data analysis using informal method. The results obtained from this research reveal social aspects including: educational aspects, sad kerthi aspects, educational aspects, arts aspects, love aspects, and development success aspects in Bali.